Recent Advances on Underwater Soft Robots - Qu, Juntian; Xu, Yining; Li, Zhenkun; Yu, Zhenping; Mao, Baijin; Wang, Yunfei; Wang, Ziqiang; Fan, Qigao; Qian, Xiang; Zhang, Min; Xu, Minyi; Liang, Bin; et al. (Advanced intelligent systems, 2024)
The ocean environment has enormous uncertainty due to the influence of complex waves and undercurrents. The human beings are limited in their abilities to detect and utilize marine resources without powerful tools. Soft robots employ soft materials to simplify the complex mechanical structures in rigid robots and adapt their morphology to the environment, making them suitable for performing some challenging tasks in place of manual labor. Due to superior flexible and deformable bodies, underwater soft robots have played significant roles in numerous applications in recent decades. Meanwhile, various technical challenges still need to be tackled to ensure the reliability and practical performance of underwater soft robots in complicated ocean environment. Nowadays, some researchers have developed underwater soft robotic systems based on biomimetics and other disciplines, aiming at comprehensive exploration of ocean and appropriate utilization of unexploited resources. This review presents the recent advances of underwater soft robots in the aspects of intelligent soft materials, fabrication, actuation, locomotion patterns, power storage, sensing, control, and modeling; additionally, the existing challenges and perspectives are analyzed as well. Advanced underwater soft robots are crucial. This article first introduces the development trend and research status of underwater soft robots, and reviews the general underwater wireless communication methods. Works about biomimetic underwater soft robots are summarized. Detailed information on intelligent soft materials, fabrication, actuation, locomotion patterns, power storage, sensing, control, and modeling is provided. Challenges and outlooks are discussed.